Rheo-NMR Spectroscopy - Schmidt, Claudia (Modern Magnetic Resonance)

Projekt „Übergang Förderschule-Beruf - Fischer, E.; Heger, M.; Laubenstein, Désirée (In: Impulse Nr. 2/3, Ausgabe 46/47)

Sprachförderung im Kindergarten - Tophinke, Doris

Junktionsstrategien in deutschen und englischen Online-Hilfen für Softwareprogramme - Tophinke, Doris; Ziegler, Evelyn (Perspektiven der Medienlinguistik: sprachliche und mediale Globalisierung in Europa)

Regional schreiben: Weblogs zwischen Orthographie und Phonographie - Tophinke, Doris (Sprechen, Schreiben, Hören - Zur Produktion und Perzeption von Dialekt und Standardsprache zu Beginn des 21. Jahrhunderts)

Measuring the relationship between supervisory authorities and banks: An assessment of the German banking sector - Paul, Stephan; Stein, Stefan; Uhde, André (Journal of Risk Managment in Financial Institutions)
The successful implementation of a harmonised regulatory framework for the global banking system is still a long way off. This mainly results from (a) different traditions in banking regulation and supervision at the national level, (b) different national emphases on regulatory sub-goals such as efficiency or the protection and promotion of national financial markets, and (c) different institutional settings and conditions. In this context, studies on the banking industry's assessment of supervisory processes and instruments highlight how effectively and efficiently individual nation states are implementing international frameworks such as Basel II and the Capital Requirements Directive for Europe. In November 2005, the German Government commissioned an evaluation of the supervisory processes and instruments of the country's banking authorities, BaFin and Bundesbank. The study aimed to determine the options for further optimising supervision, reducing regulatory burden and bureaucracy, and otherwise restricting supervision. This paper presents the most important findings from the survey, analyses significant differences in assessments given by various banking groups, empirically evaluates significant drivers of banks' overall satisfaction with banking supervision, and drafts proposals for improving banking regulation and supervision in Germany. Finally, aspects of further research are discussed.
Keywords: banking supervision; quality; assessment; banking sector

Tunable optical properties of photonic crystals and semiconductor microdisks using liquid crystals - Piegdon, Karoline A.; Matthias, Heinrich; Meier, Cedrik; Kitzerow, Heinz-Siegfried (Emerging Liquid Crystal Technologies III)

Reflektieren, aber nicht das Credo verraten. Die schwierige Aufgabe der 2. Generation feministischer Frauen - Hagengruber, Ruth Edith (Konsens)

Philosophische Grundlagenforschung für die Informatik - Hagengruber, Ruth Edith (HNI Heinz Nixdorf Institut Nachrichten)

Philosophical Basics in Computer Science: Action-Theoretical Concepts in Cooperative Systems - Hagengruber, Ruth Edith (HNI Annual Report)

Education and Philosophy - Hagengruber, Ruth Edith (UNESCO-UNEVOC Bulletin 14, no. Suppmenent 12)

Action Types in Knowledge Representation - Hagengruber, Ruth Edith (presented at the Fifth International Workshop on Philosophy and Informatics)

Sokrates im Wissensmanagement. Philosophische Grundlagen in den Computerwissenschaften - Hagengruber, Ruth Edith (Forschungsforum Paderborn)

Philosophische Grundlagen in der Informatik: Handlungstheoretische Konzepte in kooperativen Systemen - Hagengruber, Ruth Edith (HNI Jahresbericht)

Konsumentinnen und Konsumenten - politisch denkende und moralisch handelnde Akteure - Schlegel-Matthies, Kirsten (Haushalt & Bildung)

Uncertainty aversion and Preferences for Randomization: An Experimental Study - Schnedler, Wendelin; Dominiak, Adam (Economic Theory)

Ethik und Wissenschaft und ihre Anwendung: Kritik zu Hans Lenk und Matthias Maring: Ethik der Wissenschaft - Wissenschaft der Ethik - Hagengruber, Ruth Edith (Erwägen Wissen Ethik)

L'éducation en tant que ressource - Hagengruber, Ruth Edith (UNEVOC~Forum: Supplement to UNESCO-UNEVOC Bulletin)

Hilflose Maschinen und treusorgende Pflegepersonen. Über jüngste Tendenzen in der Forschung zur Mensch-Roboter-Interaktion - Weber, Jutta (Public Fictions. Wie man Roboter und Menschen erfindet)

Ethically Motivated Recommendations for EU Policies and Regulations concerning Robotics and its Convergence with Bionic and Software Agent Technologies. Deliverable 6 of the EU-Project ETHICBOTS. Emerging Technoethics of Human Interaction with Communication, Bionic and Robotic Systems (SAS 6 – 017759) - Weber, Jutta; Capurro, Rafael; Christaller, Thomas; Datteri, Edoardo; Giordani, Alessandro; Laschi, Cecilia; Mock, Michael; Nagenborg, Michael; Salvini, Pericle; Tamburrini, Guglielmo

Techno-Ethical Case-Studies in Robotics, Bionics, and Related AI Agent Technologies. Deliverable 5 of the EU-Project ETHICBOTS. Emerging Technoethics of Human Interaction with Communication, Bionic and Robotic Systems (SAS 6 – 017759) - Weber, Jutta; Capurro, Rafael; Christaller, Thomas; Datteri, Edoardo; Giordani, Alessandro; Laschi, Cecilia; Mock, Michael; Nagenborg, Michael; Salvini, Pericle; Tamburrini, Guglielmo

Sex, Service und digitale Geborgenheit. Technoimaginationen des Humanoiden zwischen Fiktion und Dienstleistungsökonomie - Weber, Jutta (genderzukunft. Zur Transformation feministischer Visionen in der Science Fiction)

Vorwort: Methodisches Denken im Kontext. Festschrift für Christian Thiel. Mit einem unveröffentlichten Brief Gottlob Freges - Peckhaus, Volker; Bernhard, Peter (Methodisches Denken im Kontext. Festschrift für Christian Thiel. Mit einem unveröffentlichten Brief Gottlob Freges)

An Efficient Time Annotation Technique in Abstract RTOS Simulations for Multiprocessor Task Migration - Zabel, Henning; Müller, Wolfgang
Complex control oriented embedded systems with hard real-time constraints require real-time operation system (RTOS) for predictable timing behavior. To support the evaluation of different scheduling strategies and task priorities, we use an abstract RTOS model based on SystemC. In this article, we present an annotation method for time estimation that supports flexible simulation and validation of real-time-constraints for task migration between different target processors without loss of simulation performance and less memory overhead.
Keywords: Execution Time Schedule Strategy Simulation Speed Task Migration Atomic Block

Präzises Interrupt Scheduling in abstrakten RTOS Modellen in SystemC - Zabel, Henning; Müller, Wolfgang (Methoden und Beschreibungs-sprachen zur Modellierung und Verifikation von Schaltungen und System)
Bei der Simulation von eingebetteten Echtzeit Systemen zur Analyse von Ausführungs- zeiten und Scheduling gibt es immer einen Kompromiss zwischen zyklengenauen Ergebnis- sen und der Laufzeit der Simulation. Mithilfe von abstrakten RTOS Modellen auf Basis von SystemC wird versucht diese Lücke zu schließen. Aktuelle Arbeiten besitzen allerdings nur unzureichende Möglichkeiten zur Modellierung von Interrupt Scheduling und ihren hard- wareabhängigen Prioritäten. Unser Ansatz verwendet zwei getrennte Scheduler für Softwa- re Task und Interrupt Service Routinen. Diese Trennung erlaubt die präzise Modellierung von Interrupt Prioritäten und Interrupt Scheduling unabhängig von dem eigentlichen RTOS Scheduler.

'Van der hemeluart vnses heren Jesu Christi volget nu hir na'. Niederdeutsche Predigten zur Himmelfahrt im Vergleich. - Wallmeier, Nadine; Wirrer, Jan (Exemplar. Festschrift für Kurt Otto Seidel.)

Human-Robot Interaction - Weber, Jutta (Handbook of Research on Computer-Mediated Communication)

„Ich bin dafür, dass...“ Kinder gewinnen Standpunkte - Büker, Petra (Praxis Deutsch)

Sprachbarrieren in der Diskussion. Eine wissenschaftsgeschichtliche Darstellung. - Lorenz, Cornelia

On the graphitisation role of oxide supports in carbon nanotube CVD synthesis - Rümmeli, M. H.; Schäffel, F.; de los Arcos de Pedro, Maria Teresa; Haberer, D.; Bachmatiuk, A.; Kramberger, C.; Ayala, P.; Borowiak-Palen, E.; Adebimpe, D.; Gemming, T.; Leonhardt, A.; Rellinghaus, B.; et al. (physica status solidi (b))

Asset Write-Offs in the Absence of Agency Problems - Garrod, Neil; Kosi, Urska; Valentincic, Aljosa (Journal of Business Finance and Accounting)
Using a large sample of small private companies, we show incremental influence ofeconomic incentives over prescriptions from accounting standards by financial statementpreparers in a code‐law setting with high alignment between financial and tax reportingand no agency problems. Contrary to predictions from standards, more profitable companiesare more likely to write‐off and the write‐off magnitude is greater, reflecting taxminimisation. Larger companies are more likely to write‐off, but the magnitude decreaseswith size, reflecting increasing political costs due to greater visibility to taxauthorities. Previous write‐off patterns and magnitudes are persistent, reflectinginstitutional learning linked to regulatory changes.

Submicrometer periodic patterns fixed by photopolymerization of dissipative structures - Hoischen, A.; Benning, S. A.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Influence of doping on the photorefractive properties of a polymer-dispersed liquid crystal - Redler, Andreas; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Phased-array cancellation of nonlinear FWM in coherent OFDM dispersive multi-span links - Nazarathy, Moshe; Khurgin, Jacob; Weidenfeld, Rakefet; Meiman, Yehuda; Cho, Pak; Noé, Reinhold; Shpantzer, Isaac; Karagodsky, Vadim (OPTICS EXPRESS)

Fast optical polarisation tracking experiment with 2 Grad trajectory length - Koch, B.; Hidayat, A.; Mirvoda, V.; Zhang, H.; Lichtinger, M.; Sandel, D.; Noé, Reinhold (ELECTRONICS LETTERS)

Ultra-fast adaptive digital polarization control in a realtime coherent polarization-multiplexed QPSK receiver - Pfau, T.; Woerdehoff, C.; Peveling, R.; Ibrahim, S. K.; Hoffmann, S.; Adamczyk, O.; Bhandare, S.; Porrmann, M.; Noé, Reinhold; Koslovsky, A.; Achiam, Y.; Schlieder, D.; et al. (2008 CONFERENCE ON OPTICAL FIBER COMMUNICATION/NATIONAL FIBER OPTIC ENGINEERS CONFERENCE, VOLS 1-8)

Fast Adaptive Polarization and PDL Tracking in a Real-Time FPGA-Based Coherent PolDM-QPSK Receiver - El-Darawy, Mohamed; Pfau, Timo; Hoffmann, Sebastian; Peveling, Ralf; Woerdehoff, Christian; Koch, Benjamin; Porrmann, Mario; Adamczyk, Olaf; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Frequency and Phase Estimation for Coherent QPSK Transmission With Unlocked DFB Lasers - Hoffmann, Sebastian; Bhandare, Suhas; Pfau, Timo; Adamczk, Olaf; Woerdehoff, Christian; Peveling, Ralf; Porrmann, Mario; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Finite Deformation Elasto-Plasticity for Simulation of Strength Difference in Adhesive Materials with an Algorithm in Principal Directions - Mahnken, Rolf (Mechanics of Advanced Materials and Structures)

Damage analysis under thermal shock loading using eddy current sensors - Sauerland, Kim-Henning; Gockel, Franz-Barthold; Mahnken, Rolf; Ferber, Ferdinand (Nondestructive Testing and Evaluation)

Thermoviscoplastic modelling of asymmetric effects for polymers at large strains - Mahnken, Rolf; Shaban, A.; Potente, H.; Wilke, L. (International Journal of Solids and Structures)

Macro modelling and homogenization for transformation induced plasticity of a low-alloy steel - Mahnken, Rolf; Schneidt, Andreas; Antretter, Thomas (International Journal of Plasticity)

Measuring mechanical parameters in glass fiber-reinforced composites: Standard evaluation techniques enhanced by photogrammetry - Koke, Isabel; Müller, Wolfgang H.; Ferber, Ferdinand; Mahnken, Rolf; Funke, Herbert (Composites Science and Technology)

Simulation of the residual stresses in the contour laser welding of thermoplastics - Potente, H.; Wilke, L.; Ridder, H.; Mahnken, Rolf; Shaban, A. (Polymer Engineering & Science)

Material forces for crack analysis of functionally graded materials in adaptively refined FE-meshes - Mahnken, Rolf (International Journal of Fracture)

Coherent optical communication: Towards realtime systems at 40 Gbit/s and beyond - Pfau, T.; Hoffmann, S.; Adamczyk, O.; Peveling, R.; Herath, V.; Porrmann, M.; Noé, Reinhold (OPTICS EXPRESS)

13 Gsamples/s 5-bit analogue-to-digital converter for coherent optical QPSK receiver - Adamczyk, O.; Noé, Reinhold (ELECTRONICS LETTERS)

32-krad/s Polarization and 3-dB PDL Tracking in a Realtime Digital Coherent Polarization-Multiplexed QPSK Receiver - Pfau, T.; El-Darawy, M.; Woerdehoff, C.; Peveling, R.; Hoffmann, S.; Koch, B.; Adamczyk, O.; Porrmann, M.; Noé, Reinhold (2008 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

5-bit 12.5 Gsamples/s Analog-to-Digital Converter for a Digital Receiver in a Synchronous Optical QPSK Transmission System - Adamczyk, O.; Noé, Reinhold (2008 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Realtime Digital Polarization and Carrier Recovery in a Polarization-Multiplexed Optical QPSK Transmission - Noé, Reinhold; Hoffmann, S.; Pfau, T.; Adamczyk, O.; Herath, V.; Peveling, R.; Porrmann, M. (2008 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

High-speed endless optical polarization stabilization using calibrated waveplates and field-programmable gate array-based digital controller - Hidayat, Ariya; Koch, Benjamin; Zhang, Hongbin; Mirvoda, Vitali; Lichtinger, Manfred; Sandel, David; Noé, Reinhold (OPTICS EXPRESS)

Realtime 40 krad/s Polarization Tracking with 6 dB PDL in Digital Synchronous Polarization-Multiplexed QPSK Receiver - El-Darawy, M.; Pfau, T.; Woerdehoff, C.; Koch, B.; Hoffmann, S.; Peveling, R.; Porrmann, M.; Noé, Reinhold (2008 34TH EUROPEAN CONFERENCE ON OPTICAL COMMUNICATION (ECOC))

12 krad/s Endless Polarization Stabilization with Lithium Niobate Component - Koch, B.; Hidayat, A.; Zhang, H.; Mirvoda, V.; Lichtinger, M.; Sandel, D.; Noé, Reinhold (2008 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Optical endless polarization stabilization at 9 krad/s with FPGA-based controller - Koch, Benjamin; Hidayat, Ariya; Zhang, Hongbin; Mirvoda, Vitali; Lichtinger, Manfred; Sandel, David; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Optical endless polarization stabilization at 9 krad/s with FPGA-based controller - Koch, Benjamin; Hidayat, Ariya; Zhang, Hongbin; Mirvoda, Vitali; Lichtinger, Manfred; Sandel, David; Noé, Reinhold (IEEE PHOTONICS TECHNOLOGY LETTERS)

Recent Advances in Coherent Optical OFDM High-Speed Transmission - Nazarathy, Moshe; Weidenfeld, Rakefet; Noé, Reinhold; Khurgin, Jacob; Meiman, Yehouda; Cho, Pak; Shpantzer, Isaac (2008 IEEE PhotonicsGlobal@Singapore)

Fast Adaptive Polarization and PDL Tracking in a Real-Time FPGA-Based Coherent PolDM-QPSK Receiver - El-Darawy, Mohamed; Pfau, Timo; Hoffmann, Sebastian; Peveling, Ralf; Wordehoff, Christian; Koch, Benjamin; Porrmann, Mario; Adamczyk, Olaf; Noé, Reinhold (IEEE Photonics Technology Letters)

Frequency and Phase Estimation for Coherent QPSK Transmission With Unlocked DFB Lasers - Hoffmann, Sebastian; Bhandare, Suhas; Pfau, Timo; Adamczyk, Olaf; Wordehoff, Christian; Peveling, Ralf; Porrmann, Mario; Noé, Reinhold (IEEE Photonics Technology Letters)

Optical Endless Polarization Stabilization at 9 krad/s With FPGA-Based Controller - Koch, Benjamin; Hidayat, Ariya; Zhang, Hongbin; Mirvoda, Vitali; Lichtinger, Manfred; Sandel, David; Noé, Reinhold (IEEE Photonics Technology Letters)

12 krad/s Endless Polarization Stabilization with Lithium Niobate Component - Koch, B.; Hidayat, A.; Zhang, H.; Mirvoda, V.; Lichtinger, M.; Sandel, D.; Noé, Reinhold (2008 DIGEST OF THE LEOS SUMMER TOPICAL MEETINGS)

Nilsson, Christina - Grotjahn, Rebecca (Die Musik in Geschichte und Gegenwart. Supplementband)

Die AdressatInnen sozialräumlich orientierter Sozialer Arbeit und der Sozialraum als Adressat – eine empirische Betrachtung - Klingler, Birte; Landhäußer, Sandra; Ziegler, Holger (Soziale Arbeit in Gesellschaft)
Die Bielefelder Arbeitsgruppe 8 Sozialarbeit/Sozialpädagogik hat in den letzten vier Dekaden deutliche Markierungen in der deutschsprachigen wie der internationalen Debatte um Soziale Arbeit gesetzt. Antriebsmotor dieser Entwicklung war und ist Hans-Uwe Otto. In diesem Band haben sich dessen Ko-Autorinnen und -Autoren aus Anlass seiner Pensionierung erstmals zu einer Gesamtschau dieser 'Bielefelder Forschungsperspektiven' auf die Soziale Arbeit versammelt. Die acht zentralen Forschungs- und Themenfelder, die von der Bielefelder AG oder unter ihrer Beteiligung in den letzten Jahrzehnten bestellt wurden, gliedern den Band. Der gemeinsame Bezugspunkt aller hier versammelten Beiträge ist die Verbindung von Sozialer Arbeit und Gesellschaft: Soziale Arbeit als professionelle Instanz ist nur in ihrem gesellschaftlichen Kontext und damit in explizit gesellschaftspolitischer Positionierung realisierbar.
Keywords: Sozialraum; Soziale Arbeit

Biomimetic Synthesis of Resorcylate Natural Products Utilizing Late Stage Aromatization: Concise Total Syntheses of the Marine Antifungal Agents 15G256ι and 15G256β - Navarro, Ismael; Basset, Jean-François; Hebbe, Séverine; Major, Sarah M.; Werner, Thomas; Howsham, Catherine; Bräckow, Jan; Barrett, Anthony G. M. (Journal of the American Chemical Society)
Keywords: Colloid and Surface Chemistry; Biochemistry; General Chemistry; Catalysis

Zwischen (trügerischer) Ruhe und fieberhafter Arbeit – Betreuung von Blended-Learning-Seminaren - Göddertz, Nina; van Treeck, Timo; Wieg, Mirco (Online Tutoring Journal, Ausgabe 2 (9))
Keywords: ILIAS; Jugendforschung

Tuning of the Optical Properties in Photonic Crystals Made of Macroporous Silicon - Kitzerow, Heinz-Siegfried; Matthias, Heinrich; Schweizer, Stefan L.; van Driel, Henry M.; Wehrspohn, Ralf B. (Advances in Optical Technologies)
It is well known that robust and reliable photonic crystal structures can be manufactured with very high precision by electrochemical etching of silicon wafers, which results in two- and three-dimensional photonic crystals made of macroporous silicon. However, tuning of the photonic properties is necessary in order to apply these promising structures in integrated optical devices. For this purpose, different effects have been studied, such as the infiltration with addressable dielectric liquids (liquid crystals), the utilization of Kerr-like nonlinearities of the silicon, or free-charge carrier injection by means of linear (one-photon) and nonlinear (two-photon) absorptions. The present article provides a review, critical discussion, and perspectives about state-of-the-art tuning capabilities.

Recent Advances in Coherent Optical OFDM High-Speed Transmission - Nazarathy, Moshe; Noé, Reinhold; Weidenfeld, Rakefet; Khurgin, Jacob; Meiman, Yehouda; Cho, Pak; Shpantzer, Isaac (2008 IEEE PHOTONICSGLOBAL@SINGAPORE (IPGC), VOLS 1 AND 2)

Optical 5 krad/s endless polarisation tracking - Hidayat, A.; Koch, B.; Mirvoda, V.; Zhang, H.; Lichtinger, A.; Sandel, D.; Noé, Reinhold (ELECTRONICS LETTERS)

Homogeneous Administration of Experiments in Material Science for Configuration, Monitoring and Analysis - Ferber, Ferdinand; Gockel, Franz-Barthold; Hampel, Thorsten; Pawlak, Thorsten; Mahnken, Rolf (Experimental Analysis of Nano and Engineering Materials and Structures)

Geometry update driven by material forces for simulation of brittle crack growth in functionally graded materials - Mahnken, Rolf (International Journal for Numerical Methods in Engineering)

On the stabilization of tetrahedral finite elements using volume and area bubble functions - Caylak, Ismail; Mahnken, Rolf (PAMM)

Experimentelle Untersuchungen zum Thermoschock beim Hybridumformprozess - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Simulation of asymmetric effects for shape memory alloys - Wilmanns, Stefan; Mahnken, Rolf (PAMM)

Fast optical endless polarization tracking with LiNbO3 component - Hidayat, A.; Koch, B.; Mirvoda, V.; Zhang, H.; Bhandare, S.; Ibrahim, S. K.; Sandel, D.; Noé, Reinhold (2008 CONFERENCE ON OPTICAL FIBER COMMUNICATION/NATIONAL FIBER OPTIC ENGINEERS CONFERENCE, VOLS 1-8)

A Limit Relation for Dunkl-Bessel Functions of Type A and B - Rösler, Margit; Voit, Michael (Symmetry, Integrability and Geometry: Methods and Applications)
Keywords: Geometry and Topology; Mathematical Physics; Analysis

Meditationen, Geheimnisse, Zufälle: Messiaens Konzept der langage communicable - Grotjahn, Rebecca (organ. Journal für die Orgel)

Multiple-Channel Signal Detection using the Generalized Coherence spectrum - Ramírez, D.; Vía, J.; Santamaría, I. (Proc.\ IAPR Work. Cognitive Information Process.)
Recently, a generalization of the magnitude squared coherence (MSC) spectrum for more than two random processes has been proposed. The generalized MSC (GMSC) spectrum definition, which is based on the largest eigenvalue of a matrix containing all the pairwise complex coherence spectra, provides a frequency-dependent measure of the linear relationship among several stationary random processes. Moreover, it can be easily estimated by solving a generalized eigenvalue problem. In this paper we apply the GMSC spectrum for detecting the presence of a common signal from a set of linearly distorted and noisy observations. Specifically, the new statistic for the multiple-channel detection problem is the integral of the square root of the GMSC, which can be estimated as the sum of the $P$ largest generalized canonical correlations (typically $P=1$ is enough in practice). Unlike previous approaches, the new statistic implicitly takes into account the spectral characteristics of the signal to be detected (e.g., its bandwidth). Finally, the performance of the proposed detector is compared in terms of its receiver operating characteristic (ROC) curve with the generalized coherence (GC) showing a clear improvement in most scenarios.

Performance analysis of OFDM-IDMA systems with peak-power limitation - Tong, Jun; Guo, Qinghua; Ping, Li (IEEE 10th\ Int.\ Symp.\ Spread Spectrum Techn.\ & Appl.)
This paper is concerned with orthogonal frequencydivision multiplexing interleave-division multiple-access (OFDMIDMA) systems over frequency-selective fading channels. Deliberate clipping is applied to reduce the peak-to-average power ratio (PAPR) of each user’s transmitted signal. An iterative multiuser detection (MUD) technique is developed to recover the performance loss due to clipping. A semi-analytical signal-to-noise ratio (SNR) evolution technique is proposed, which can provide quick and accurate prediction of the iterative MUD performance. Numerical results show that the performance of OFDM-IDMA is not sensitive to the frequency selectivity of channels, and OFDM-IDMA is more power-efficient than other alternative multi-carrier transmission techniques

Impact of signaling schemes on iterative linear minimum-mean-square-error detection - Ping, Li; Tong, Jun; Yuan, Xiaojun; Guo, Qinghua (Proc.\ IEEE Global Telecomm.\ Conf.)
In this paper, we study the iterative detection problem for a coded system with multi-ary modulation. We show that, with iterative linear minimum-mean-square-error (LMMSE) detection, superposition coded modulation (SCM) can provide performance superior to that with other traditional signaling schemes used in trellis coded modulation (TCM) and bit-interleaved coded modulation (BICM). This finding provides a useful guideline for system design considering inter-symbol interference (ISI) and other forms of interference. Simulation results are provided to illustrate the efficiency of the iterative LMMSE detection with different signaling schemes.

Bounds on the Degree of Impropriety of Complex Random Vectors - Schreier, Peter J. (IEEE Signal Process.\ Lett.)
A complex random vector is called improper if it is correlated with its complex conjugate. We introduce a measure for the degree of impropriety, which is a function of the canonical correlations between the vector and its complex conjugate (sometimes called the circularity spectrum). This measure is invariant under linear transformation, and it relates the entropy of an improper Gaussian random vector to its corresponding proper version. For vectors with given spectrum, we present upper and lower bounds on the attainable degree of impropriety, in terms of the eigenvalues of the augmented covariance matrix.

A time-frequency formula for LMMSE filters for nonstationary underspread continuous-time stochastic processes - Wahlberg, Patrik; Schreier, Peter J. (Proc. 16th\ European Signal Process.\ Conf.)
We study linear minimum mean square error (LMMSE) filters for estimating a nonstationary second-order continuous-time stochastic process from a noisy observation. The equation for the optimal filter is treated in the Weyl symbol domain, and the involved Weyl symbols are assumed to belong to certain modulation spaces. By discretizing this equation using a Gabor frame we transform it into a matrix equation and obtain a formula for the filter by matrix inversion. The inverse matrix has off-diagonal decay at a rate that increases the more underspread the process is.

Bericht zum XXI. Deutschen Kongress für Philosophie ‚Lebenswelt und Wissenschaft' - Essen, 15.-19.09.2008 - Alpsancar, Suzana; Denker, Kai; Kaminski, Andreas; Rölli, Marc; Sabrowski, Maxine; Hetzel, Andreas

Paartanz als nonverbale Kommunikation und sein (Inter-?) Subjekt. Theoretische Skizze eines Forschungsvorhabens. - Haller, Melanie; Fleischle-Braun, Claudia; Stabel (Hg.), Ralf (TanzForschung und TanzAusbildung. Dokumentation des Jubiläumssymposiums der Gesellschaft für Tanzforschung im Oktober 2007, Hamburg, S. 132-139)

Café Buenos Aires und Galeria del Latino. Zur Translokalität und Hybridität städtischer Tanzkulturen - Haller, Melanie; Funke-Wieneke, Jürgen; Klein (Hg.), Gabriele (Bewegungsraum und Stadtkultur. Sozial- und kulturwissenschaftliche Perspektiven, Bielefeld 2008, S.51-74 (zusammen mit Gabriele Klein))

Die 'Natur der Subjekte'. Subjektivierungsprozesse im Tanz - Haller, Melanie; Rehberg (Hg.), Karl-Siegbert (Die Natur der Gesellschaft. Verhandlungen des 33. Kongresses der Deutschen Gesellschaft für Soziologie 2006), Frankfurt a. M., S. 2734-2747 (zusammen mit Gabriele Klein))

Der einzelne Schritt wird zum Erlebnis“ oder warum tanzt der Mensch - Haller, Melanie (In: Ästhetik und Kommunikation, Hf. 146, 40 Jahrgang, S. 96-97)

The impact of minimum taxation by an imputable wealth tax on capital budgeting and business strategy of German companies - Sureth-Sloane, Caren; Maiterth, Ralf (Review of Managerial Science)

Steuern und Risikobereitschaft in Modellen irreversibler Investitionen - Niemann, Rainer; Sureth-Sloane, Caren (Journal für Betriebswirtschaft)

UV-photopolymerisation of poly(methyl methacrylate)-based inorganic–organic hybrid coatings and bulk samples reinforced with methacrylate-modified zirconium oxocluster - Graziola, Francesco; Girardi, Fabrizio; Bauer, Matthias; Di Maggio, Rosa; Rovezzi, Mauro; Bertagnolli, Helmut; Sada, Cinzia; Rossetto, Gilberto; Gross, Silvia (Polymer)
Keywords: Polymers and Plastics; Materials Chemistry; Organic Chemistry

Toward Designing a Robot that Learns Actions from Parental Demonstrations - Nagai, Yukie; Muhl, Claudia; Rohlfing, Katharina (The 2008 IEEE International Conference on Robotics and Automation)
How to teach actions to a robot as well as how a robot learns actions is an important issue to be discussed in designing robot learning systems. Inspired by human parent-infant interaction, we hypothesize that a robot equipped with infant-like abilities can take advantage of parental proper teaching. Parents are known to significantly alter their infant-directed actions versus adult-directed ones, e.g. make more pauses between movements, which is assumed to aid the infants’ understanding of the actions. As a first step, we analyzed parental actions using a primal attention model. The model based on visual saliency can detect likely important locations in a scene without employing any knowledge about the actions or the environment. Our statistical analysis revealed that the model was able to extract meaningful structures of the actions, e.g. the initial and final state of the actions and the significant state changes in them, which were highlighted by parental action modifications. We further discuss the issue of designing an infant-like robot that can induce parent-like teaching, and present a human-robot interaction experiment evaluating our robot simulation equipped with the saliency model.
Keywords: icra08

“Try something else!” — When users change their discursive behavior in human-robot interaction - Lohse, Manja; Rohlfing, Katharina; Wrede, Britta; Sagerer, Gerhard
This paper investigates the influence of feedback provided by an autonomous robot (BIRON) on users’ discursive behavior. A user study is described during which users show objects to the robot. The results of the experiment indicate, that the robot’s verbal feedback utterances cause the humans to adapt their own way of speaking. The changes in users’ verbal behavior are due to their beliefs about the robots knowledge and abilities. In this paper they are identified and grouped. Moreover, the data implies variations in user behavior regarding gestures. Unlike speech, the robot was not able to give feedback with gestures. Due to the lack of feedback, users did not seem to have a consistent mental representation of the robot’s abilities to recognize gestures. As a result, changes between different gestures are interpreted to be unconscious variations accompanying speech.
Keywords: discursive behavior; autonomous robot; BIRON; man-machine systems; robot abilities; robot knowledge; user gestures; robot verbal feedback utterance; speech processing; user verbal behavior; service robots; human-robot interaction; human computer interaction; gesture recognition

Parental Action Modification Highlighting the Goal versus the Means - Nagai, Yukie; Rohlfing, Katharina (The IEEE 7th International Conference on Development and Learning)
Parents significantly alter their infant-directed actions compared to adult-directed ones, which is assumed to assist the infants’ processing of the actions. This paper discusses differences in parental action modification depending on whether the goal or the means is more crucial. When demonstrating a task to an infant, parents try to emphasize the important aspects of the task by suppressing or adding their movement. Our hypothesis is that in a goal-crucial task, the initial and final states of the task should be highlighted by parental actions, whereas in a means-crucial task the movement is underlined. Our analysis using a saliency-based attention model partially verified it: When focusing on the goal, parents tended to emphasize the initial and final states of the objects used in the task by taking a long pause before/after they started/fulfilled the task. When focusing on the means, parents shook the object to highlight it, which consequently made its state invisible. We discuss our findings regarding the uniqueness and commonality of the parental action modification. We also describe our contribution to the development of robots capable of imitating human actions.

Cognitive Foundations - Rohlfing, Katharina (Handbook of Communication Competence)

Computational Analysis of Motionese: What can infants learn from parental actions? - Nagai, Yukie; Rohlfing, Katharina (The 16th International Conference on Infant Studies)

Language acquisition — a multimodal avenue - Rohlfing, Katharina (The Bielefeld Introduction to Applied Linguistics)

Single-photon level ultrafast all-optical switching - Han, Xiao-Feng; Weng, Yu-Xiang; Wang, Rui; Chen, Xi-Hao; Luo, Kai Hong; Wu, Ling-An; Zhao, Jimin (Applied Physics Letters)

Multikriteriale Zielerreichung im naturwissenschaftsbezogenen Sachunterricht der Grundschule – Eine Studie zum Einfluss von Strukturierung in schülerorientierten Lehr-Lernumgebungen auf das Erreichen kognitiver, motivationaler und selbstbezogener Zielsetzungen. Inaugural-Dissertation zur Erlangung des akademischen Grades des Doktors in den Erziehungswissenschaften an der Westfälischen Wilhelms-Universität Münster - Blumberg, Eva

Rätsel und Lektüren: Zur Zyklizität von Robert Schumanns Liederkreis Myrthen op. 25 - Grotjahn, Rebecca (Gattungsgeschichte als Kulturgeschichte. Festschrift für Arnfried Edler)

Fundstück: Musikwissenschaftliche Genderforschung im 19. Jahrhundert? - Grotjahn, Rebecca (Feste - Opern - Prozessionen)

Eine ‚Stimme von fast männlicher Färbung – Zarah Leander und die nationalsozialistische Geschlechterordnung - Grotjahn, Rebecca (Performativität und Performance. Geschlecht in Musik, Theater und MedienKunst)

Der Wirkungskreis des Weibes. Zur Funktion frauenfeindlicher Rede in der Zauberflöte - Grotjahn, Rebecca (Wider die Frau. Zur Geschichte und Funktion misogyner Rede)